The Implementation of Blended Learning in Teaching Reading at English Postgraduate Program Universitas Negeri Semarang - Putri, Dinda Rahmadhani; Frimadhona Syafri; Zulfa Shakiyya (English Education Journal, 2024)
The advancement of technology, communication, and data, particularly the internet, has attracted the attention of Indonesian educators. Blended learning has become popular across all school levels in this quickly changing manner of teaching. In the context of teaching English as a foreign language, teachers must adapt to the use of technology in their instructional activities to successfully fulfil the learning objectives. This study describes the use of blended learning in an Engagement Reading class at Universitas Negeri Semarang Language Education Department. The researchers collected data through observation, interviews, and documentation. The study's findings indicate that the stages of field knowledge building, text modelling, joint text creation, and autonomous text construction are used in the reading class. Elena, WhatsApp, Zoom, Google, and Chrome are used to help with the teaching and learning process. Blended learning can make students become active learners because the students can get the other additional information from the internet during the online learning it is effective to make the students enjoy the learning process and do not feel bored with the monotonous learning situation. In addition, the virtual class has easy access anywhere and anytime in different places at the same time and makes it easier for teachers to create archives in digital form. Due to the multi-sources in blended learning, it helps the students to develop their daily reading activity. However, they continue to encounter a difficulty that many students in Indonesia face: internet access and credit quota.